RANZCOG CREI Consensus Statement on treatment of Ovarian Hyperstimulation Syndrome. (17th August 2015) - Kwik, Michele; Karia, Sonal; Boothroyd, Clare
<x xml:space="preserve">Abstract</x> Background Ovarian hyperstimulation syndrome (OHSS) is an uncommon but important iatrogenic condition associated with considerable morbidity and a small risk of mortality. This document gathers the consensus of a group of fertility subspecialists to aid health professionals in the development of protocols and guidelines for the management of women with OHSS. Aim To produce evidence‐based consensus statements on the treatment of ovarian hyperstimulation syndrome (OHSS). Methods The CREI Consensus Group met in 2013 and 2014 and identified issues for inclusion and review. Review of the available evidence was conducted and consensus statements prepared. Areas of dissent of expert opinion and for further research were noted. Results There is a paucity of good data regarding the treatment of this condition, and much of the treatment is supportive in nature. Most of the management recommendations are based on good clinical practice points, rather than evidence from randomised trials. Conclusion OHSS is an uncommon but serious condition for which there are a number of proven preventative strategies. Once OHSS is present, the treatment of OHSS is mainly supportive, and more research is required to elucidate treatment options targeted specifically at the main causative factors, to better treat the condition.